NILAI-NILAI PENDIDIKAN TAUHID DALAM KISAH ASHABUL UKHDUD SURAT AL-BURUJ PERSPEKTIF IBN KATSIR DAN HAMKA - M Muthoifin; Fahrurozi Fahrurozi (Profetika: Jurnal Studi Islam, 2018)
Tawhed is to insulate God in creation, worship and name and natures. he must be awake with the best of everything that can divert it. Because tawhed is a very basic and fundamental thing for a Muslim's life. Tawhid is the determinant of a person both in the life of the world and the hereafter, happy or miserable, safe or wretched. tawhed became one of the potential that brought every human being when he was born in the world, the need for educational efforts so that potential is maintained. This study aims to determine the concept of tawhed education in the story of ashabul ukhdud. So important is the story that Allah mentioned in the Qur'an. The second goal is to implement the concepts of Tawhed education in Islamic education. Because the most important element in Islamic education is tawhed education, education that teaches every practice, behavior, purpose of life is only God. The results showed that the ideal Islamic education is very concerned about the implementation of tawhid education, because tawhed is the spirit of Islamic education which consists of three principal, first, tawhed rububiyyah education contained therein such as human nature as the basis of tawhed education, the natural sign as a means of tawhed education, reward and punismant in tawhed education. Secondly, the education of tawhed uluhiyyah such as, the role of educators in tawhid education, evaluation in tawhed education and tawhed education throughout life. Then the third tawhid asthma 'wasifat (names and natures of Allah) education.Tauhid yaitu mengesakan Allah dalam rububiyyah, uluhiyyah dan asma’ washifat, harus terjaga dengan sebaik-baiknya dari segala yang bisa menyelewengkannya. Karena tauhidmerupakan perkara yang sangat pokok dan mendasar bagi kehidupan seorang muslim. Tauhid merupakan penentu seseorang baik di kehidupan dunia maupun akhirat, bahagia atau sengsara, selamat atau celaka. Tauhid menjadi salah satu potensi yang dibawa setiap manusia ketika ia dilahirkan didunia, perlu adanya usaha pendidikan agar potensi itu tetap terjaga. Penelitian ini bertujuan untuk mengetahui konsep pendidikan tauhid dalam kisah ashabul ukhdud. Begitu pentingnya kisah tersebut sehingga Allah menyebutkannya dalam Al-Qur’an. Tujuan kedua yaitu untuk mengimplemen-tasikan konsep-konsep pendidikan tauhid dalam pendidikan Islam. Karena unsur terpenting dalam pendidikan Islam adalah pendidikan tauhid, pendidikan yang mengajarkan setiap amalan, perilaku, tujuan hidup hanya Allah. Hasil penelitian menunjukkan bahwa pendidikan Islam yang ideal sangatlah memperhatikan pelaksanaan pendidikan tauhid, karena tauhid merupakan ruh dari pendidikan Islam yang terdiri dari tiga pokok, pertama, pendidikan tauhid rububiyyah yang terkandung didalamnya seperti fitrah manusia sebagai dasar pendidkan tauhid, ayat kauniah sebagai sarana pendidikan tauhid, Targhib dan tarhib dalam pendidikan tauhid. Kedua, pendidikan tauhid uluhiyyah seperti, peran pendidik dalam pendidikan tauhid, evaluasi dalam pendidikan tauhid dan pendidikan sepanjang hayat. Kemudian yang ketiga pendidikan tauhid asma’ wasifat.